OPTIMALISASI PERFORMA AKSES HALAMAN WEB DENGAN MEMANFAATKAN TEKNIK LOAD BALANCING PADA GOOGLE CLOUD - Ivan Firmansyah; Fietyata Yudha (Jurnal Pendidikan Teknologi Informatika dan Sains, 2021)
Web pages are one of the access doors for internet users to be able to access resources on the internet. The increasing number of web page users today, demands that web services also be faster and more responsive in handling user requests. The increasing number of requests by the number of users causes the web to be overloaded so that it is necessary to share the load on the so that the workload of the machine becomes lighter. One solution offered is to perform load balancing on the Google Cloud platform. By configuring this platform allows the machine to perform load sharing automatically when it reaches a certain threshold. Based on experiments conducted, automatic load sharing on the Google Cloud platform can be done by configuring Load Balancing. Based on the testing process conducted 15 times shows that the platform can perform load sharing automatically in accordance with the specified limit